Production management : methods and studies - Lev, Benjamin (North-Holland AmsterdamNL, 1986)
Contains papers which examine effective ways of managing the Production Management process. These cover four subject areas representing the historical development of production management. The first group of papers deal with inventory topics. The second and third deal with flexible manufacturing, scheduling, computer applications, and simulation. The final group deals with artificial intelligence, robotics, and expert systems.